Energy harvesting using ocean data acquisition system (ODAS) buoy for coral reef monitoring - Omar, Abdul Hakim (2019)
The threat to coral reefs in the ocean and coastal areas is growing, the main thing that threatens coral reefs is weather changes and human activities. If this is not in concern it will damage the coral reef which is the habitat of most marine life. There are several methods to monitor the coral reef status, one of the methods is by using Ocean Data Acquisition System (ODAS) Buoys. Generally, the buoy is a system that used to monitor and collect data for oceanographic and meteorological research purposes. The long-term environmental anomalies study will have required lots of energy due to the usage of sensors and devices. The potential energy of solar and wind to generate electricity for use to extend the life of the buoy used for the duration of the monitoring possible for a day, a week, or a year without having to come to change the existing energy supply on the buoy. Hence the solar wind hybrid system is analyse using Matlab to see how far the solar wind hybrid can produce the energy. Solar irradiation weather data and wind speed taken from NASA POWER database for different locations such as Pulau Perhentian, Pulau Besar, Labuan Island and Sandakan coastline. After that the result acquired were compared to the calculated data. The result of the calculation indicates that Labuan Island and Sandakan coast produces high energy ranging from 400W to 700W which can accommodate the amount of burden demanded. While the results obtained from the simulation shows that the energy produced is far different from the energy generated by the equation calculation. This matter may be caused by several factors that exist in the simulation parameter, this cause by the non-matching with the equation used and the wind speed in the location recoded is not strong enough to move the wind turbine.